Plac1+ Tumor Cell‐Treg Interplay Supports Tumorigenesis and Progression of Head and Neck Cancer - Xiaoyan Meng; Zhonglong Liu; Lu Zhao; Ran Li; Luoman Gan; Liren Cao; Jingjing Sun; Lingfang Zhang; Yue He (Advanced Science)
Abstract Cancer/testis antigen (CTA) family is restricted to germline and tumor cells and plays an important role during cancer initiation and progression. Five single‐cell and two bulk RNA‐seq datasets are integrated to screen genes in the CTAs family, revealing that Placenta specific protein 1 (Plac1) is specifically expressed in head and neck squamous cell carcinoma (HNSCC) cells. Sp1 Transcription (SP1) is identified as a specific regulator of Plac1, which is confirmed by cleavage under targets and tagmentation (CUT&Tag)‐seq. With in vitro experiments, in vivo subcutaneous tumor, and a transgenic autochthonous tumor model, it is revealed that Plac1 expression promotes HNSCC progression by inducing epidermal growth factor receptor endocytosis and recycling to increase PI3K/AKT signaling pathway activity. Then, it is revealed that Plac1+ tumor cells recruit CD4+ T cells via CXCL11/CXCR3 and induce Treg differentiation via PVR/TIGIT, which in turn activates the tumorigenic signaling of Plac1+ tumor cells via LTA/LTBR and forms a reciprocal protumor loop. These findings provide insights into molecular features of CTAs in HNSCC and facilitate the development of personalized treatment strategies.